Gestão de transferência de inovações tecnológicas para empresas do setor produtivo: complexidade no relacionamento entre organizações de culturas diferentes - Alvim, Daisy Campos (2007)
The motivation of this study is based on the expectation of understanding, at least in part, the reason why the brazilian academic production ¿ which is among the largest if compared to the developing countries, has not been translated in a useful way into concrete technology transference for the production sector. The supposition that different cultures and subcultures, in terms of values, behavior, practices among organizations and groups of selected actors involved in that process,- which is the central problem of this study, and peculiar to the technology context, has elected that relationship process the object of this research this study theoretical fundaments rely on culture and technology to analyze the subcultures which manifest themselves through the typified groups of researchers, in the public organizations, small scale employers, acting on technology based companies in the private sector (ebts) and mediators. Who also act in the process the preliminary step was the case study. Several qualitative methods an procedures were used. And the investigation has advanced toward interacting interviews, at the end added by the focal group method. The conclusions reject the existence of incompatibility among the subject groups points of view, however, points out some divergent values, the presence of mutual stereotypes and also confirms the supposition that the research platform is strongly influenced by the financial factor. Although, the study reveals that the presence of common objectives which lay behind the cited divergences make possible to present a core of practical suggestions to implement the studied relationships for the benefit of the production sector as well. The peculiarities perceived while dealing with that singular context suggest futures research to clarify possible new and obscure areas in that complex relationships.